Constrained consumer practices and food safety concerns in Hanoi. (2nd May 2014) - Wertheim‐Heck, Sigrid C.O.; Vellema, Sietze; Spaargaren, Gert
Abstract Food safety is a widely recognized concern in Vietnam. Public officials, companies and consumers find different ways to address risks of pesticide residues and bacterial contamination related to the use of fresh vegetables in daily diets. The response of the government to these food safety risks includes the modernization and regulation of the food retail system. However, reforms that aim to offer a controlled and predictable provision of fresh vegetables through supermarkets seem to contrast with the daily consumer practices in a dynamic city as Hanoi; over 95% of vegetables is still being purchased at long‐established open‐air markets, importantly the informal and unhygienic street markets. Using a practices theory approach, this paper aims to explain this persistence of street‐market shopping for vegetables. Detailed accounts of consumer practices, case studies at different retailing sites and daily logbooks of consumers demonstrate that the way consumers cope with food safety risks is largely shaped by the temporal and spatial constraints of their daily shopping practices. We identified how vegetable shopping is either enjoyed as social interaction within the local community or is regarded a time‐consuming activity that conflicts with other activities in everyday life. Our findings indicate how these constraints constitute a reinforcing mechanism for the persistence of uncontrolled and unhygienic street markets. To make policy responses to food safety risks both more realistic and effective, it is essential to connect to and accommodate the daily realities of consumers managing time and space in a modernizing city rather than to impose an ideal, typical market exclusively driven by the wish to control food safety risks.